PENERAPAN GERAKAN NEW NORMAL PADA ERA COVID 19 SERTA PERKEMBANGAN PEREKONOMIAN DI PASAR ABC - Nafisatul Hasanah; Andreas Yoshiro Ogawa; Chrisjunianti Chrisjunianti; Delicia Olivian; Delvin Delvin; Eny Eny; Hendru Hendru; Rosalinda Rosalinda; Vincent Vincent (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
In this COVID19 pandemic period, there are some citizens who understand the danger of this virus. They prefer to stay at home rather than go outside the house. Hence there is a decreasing profit that is suffered by the sellers in the market ABC. But there are also citizens who still belittle the danger of this virus maybe. According to the sellers of market ABC, there are still people who don't follow the health protocol and this causes anxiety and worries of the sellers in the market ABC. The method that writers use in this report is science and technology as an information platform that is sharing information with citizens. Writers will share information about COVID19 and how to start a new normal life to increase the profit of the sellers. By sharing information writers hope that this platform can increase the consciousness of citizens.